Carbonate or ether based electrolyte for Li-Se batteries: An in-situ study of intermediate polyselenide formation. (10th September 2021) - Mutlu, Tutku; Demir-Cakan, Rezan
Highlights: Mechanism of Li-Se batteries is investigated by in-situ electrochemical tools. In-situ cycling voltammetry (CV) and impedance (EIS) analyses are employed. Self-discharge phenomenon is investigated by open circuit voltage monitoring. Formation of dissolved polyselenides are evident in Ether-based electrolytes. Carbonate-based can be used in Li-Se batteries. Abstract: Li-Se batteries have recently been concidered as one of the most promising battery systems to satisfy the future energy storage needs. On the other hand, in order to further improve the electrochemical cell performances, understanding of the Li-Se cell working mechanism, especially focusing on the formation of dissolved Li polyselenides, is essential. In this work, an in-situ study of intermediate polyselenide formation based on the 4-electrode cycling voltammetry (CV) and 3-electrode electrochemical impedance spectroscopy (EIS) are used to detect the existence of polyselenides in carbonate and ether-based electrolytes. CV measurements reveal the presence of dissolved polyselenide intermediate formations in ether-based solvent while no signatures are observed in carbonate-based electrolytes. Similar findings are also observed by EIS measurements as well as investigating the self-discharge behavior. Therefore, these two electrochemical characterizations can be easily implemented as prompt and cost-effective techniques to investigate the impact of the electrolyte solvents. Contrary to the Li-S counterparts, the outcome of the work suggests that carbonate-based electrolytes can be simply employed in the field of Li-Se batteries. Graphical abstract: It is evident by the in-situ CV and EIS analyses that polyselenides species are soluble in ether based electrolytes not in carbonate based. Unlike sulfur, selenium can be operated into cost-effective carbonate-based electrolytes without any electrolyte degradation. Image, graphical abstract